2008
DOI: 10.1007/s10725-008-9302-7
|View full text |Cite
|
Sign up to set email alerts
|

Coloured hailnets alter light transmission, spectra and phytochrome, as well as vegetative growth, leaf chlorophyll and photosynthesis and reduce flower induction of apple

Abstract: In view of alleged positive effects of coloured (red) hailnets on phytochrome, photosynthesis, yield and fruit quality, the objective of the present work was to investigate a range of red and green hailnets using apple as a model crop with cvs. 'Pinova' and 'Fuji Kiku 8'. Light transmission of green or red hailnets peaked between 500 and 570 nm (green) or above 570 nm (red-orange) and was reduced by 12% (white) or 14% (red-white), 18% (red-black) and 23% (green-black) hailnets; there were no effects on phytoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 4 publications
5
45
1
2
Order By: Relevance
“…Changes in leaf chlorophyll content were also detected under different light quality conditions in citrus trees: plants under nets with more B light proportion had the greatest leaf chlorophyll a, b and total chlorophyll content, compared to those with more R light proportion (Li and Syvertsen, 2006). In apple trees, leaf chlorophyll synthesis under nets with more R and G light transmission was up to 46% highest (Solomakhin and Blanke, 2008). Recent studies demonstrated prolonged exposition of apple leaves under nets with more light transmission in the B spectra increased the leaf stomatal conductance and leaf transpiration (Bastías et al, 2011), probably by direct effect of B light on stimulation of stomatal opening has been previously reported (Farquhar and Sharkey, 1982;Shimazaki et al, 2007).…”
Section: Plant Responses To Light Quality In Fruit Treesmentioning
confidence: 62%
See 2 more Smart Citations
“…Changes in leaf chlorophyll content were also detected under different light quality conditions in citrus trees: plants under nets with more B light proportion had the greatest leaf chlorophyll a, b and total chlorophyll content, compared to those with more R light proportion (Li and Syvertsen, 2006). In apple trees, leaf chlorophyll synthesis under nets with more R and G light transmission was up to 46% highest (Solomakhin and Blanke, 2008). Recent studies demonstrated prolonged exposition of apple leaves under nets with more light transmission in the B spectra increased the leaf stomatal conductance and leaf transpiration (Bastías et al, 2011), probably by direct effect of B light on stimulation of stomatal opening has been previously reported (Farquhar and Sharkey, 1982;Shimazaki et al, 2007).…”
Section: Plant Responses To Light Quality In Fruit Treesmentioning
confidence: 62%
“…In apple orchards, red net improved fruit size compared to black net (Shahak et al, 2008). Solomakhin and Blanke (2008) also reported increased apple fruit size under colored nets, but without effect on yield. In peach, fruit grown under red nets were firmer, sweeter and fruit size was also improved (Shahak et al, 2008), while in highbush blueberries (Vaccinium corymbosum L.), red and white nets increased the number of fruits and yield per plant in comparison with traditional black net (Retamales et al, 2008;Lobos et al, 2012).…”
Section: Manipulation Of Light Quality In Orchard Systemsmentioning
confidence: 89%
See 1 more Smart Citation
“…In experiments carried out with apple (Malus domestica Borkh. ), induction of flowering was inhibited by plastics of different colors, demonstrating that the quality of solar radiation is an important factor in variables of agronomic relevance in this crop (Solomakhin & Blanke, 2008).…”
Section: Discussion Cropping Systemsmentioning
confidence: 96%
“…el efecto positivo de la radiación difusa sobre el intercambio gaseoso de la planta puede ser atribuido a que estas condiciones micro-climáticas de luz resultan favorables en la reducción de la temperatura de la hoja promoviendo así la apertura estomática (URBaN et al, 2007).…”
Section: Materiales Y Métodos Diseño Experimental Y Manejos Del Huertounclassified